Linking political and feminist ideology with openness towards non-binary gender: The development and initial validation of a scale to measure subjective Openness towards Non-Binary Gender (ONBG). Issue 8 (17th November 2021) - Molin, Améthyste; Simond, Amélie; Sato, Sayaka; Jaeggi, Tiziana; Gygax, Pascal Mark; Meuwly, Nathalie
ABSTRACT: We present a preliminary validation of a newly built questionnaire aimed at evaluating people's openness towards the notion of non-binary gender. To explore the validity of our questionnaire, we ran a principal component analysis to evaluate the existence of three overarching dimensions ( Gender Categories, Gender Fluidity, and Gender Definitions) that were at the very foundation of our questionnaire. We also explored the link between our questionnaire and measures of one's political orientation and feminist identification. In all, our questionnaire was found to have an acceptable level of reliability, and as such, constitutes an important tool for better understanding people's attitudes towards non-binary gender.